2022
DOI: 10.1039/d1ja00448d
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS exploration of photochemically generated species of Os, W and Ru from reductive and oxidative media

Abstract: The volatile synthetic products of photochemical vapor generation (PVG) of Os(IV) and W(VI) have been confirmed by GC-MS. Osmium tetroxide has been identified as the species generated from an oxidizing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In relatively older studies, formation of Ir(CO) 4 H was reported when water containing IrCl 3 was used for the preparation of other iridium carbonyls and detected as a very volatile compound, 51 including the direct evidence by Whyman, 52 who used IR spectroscopy to investigate reactions of Ir 4 (CO) 12 under various pressures of CO and H 2 and found no evidence for formation of Ir 2 (CO) 8 . 53 To the best of our knowledge, successful GC−MS detection of any iridium carbonyl has not yet been achieved (including our most recent attempts), 54 and there is also no MS spectrum available in the NIST database. 55 Hence, identification of the product of PVG may be challenging despite its relatively good stability based on experience generated in this study.…”
Section: Figures Of Meritmentioning
confidence: 99%
“…In relatively older studies, formation of Ir(CO) 4 H was reported when water containing IrCl 3 was used for the preparation of other iridium carbonyls and detected as a very volatile compound, 51 including the direct evidence by Whyman, 52 who used IR spectroscopy to investigate reactions of Ir 4 (CO) 12 under various pressures of CO and H 2 and found no evidence for formation of Ir 2 (CO) 8 . 53 To the best of our knowledge, successful GC−MS detection of any iridium carbonyl has not yet been achieved (including our most recent attempts), 54 and there is also no MS spectrum available in the NIST database. 55 Hence, identification of the product of PVG may be challenging despite its relatively good stability based on experience generated in this study.…”
Section: Figures Of Meritmentioning
confidence: 99%
“…To date, mainly low molar mass organic acids, primarily formic and acetic acid, have been employed for this purpose as their photolysis yields strongly reducing radical species (H • , R • , and CO 2 •– ) and aquated electrons (e (aq) – ). , These subsequently interact with the ionic analytes to ultimately form volatile free atoms (Hg 0 ), hydrides, carbonyls, or alkylated derivatives, depending on the element and photochemical medium used. Oxidative conditions have also been advantageously used for the PVG of volatile OsO 4 from dilute peroxide, nitric acid, or pure water. …”
Section: Introductionmentioning
confidence: 99%
“…Oxidative conditions have also been advantageously used for the PVG of volatile OsO 4 from dilute peroxide, nitric acid, or pure water. 3 5 …”
Section: Introductionmentioning
confidence: 99%
“…Photochemical vapor generation (PVG) is utilizing generated radicals and aqueous electrons by photodecomposition of low-molecular-weighted organic compounds for converting elements into semivolatile/volatile species, which is regarded as an alternative sample introduction technique in atomic spectrometry. Over the past two decades, many efforts have focused on expanding the range of PVG elements and increasing the yield of analytes. Great progress has been made in improving the hardware design of PVG reactors and gas–liquid separators (GLSs) and photochemical mechanisms. , Recent research has demonstrated that transition metals (including Fe, Co, Ni, Cu, Cd, Mn, and V) in PVG systems can increase the efficiencies of elements, with improvements ranging from 1.1 to 30,000 folds. As a result, PVG-based methods can provide better performance for element detection in terms of analytical sensitivity and tolerance to interferences from sample matrices. Furthermore, synergistic effects were observed between different transition-metal ions, including Cu­(II) and Co­(II) for Mo detection, Fe­(II) and Mn­(II) for Te­(IV) detection, and Co­(II) and Cd­(II) for the detection of Re, Ru, Ir, and Os. Similar effects were found with ferric ions and nano-TiO 2 for Te detection and with Cu­(II) and Cl – for Ge detection .…”
Section: Introductionmentioning
confidence: 99%